IMAGERY IS A COMPONENT OF THE CONNOTATION OF THE NOMINATIVE UNIT - N.A.Nematova (Scholar Express Journal, 2023)
This article focuses on the importance of nominative units found in the speech of the hero in fiction. The national connotativeness of the images used in the speech is discussed in the translated work. The theories of our scientists who conducted scientific research in this regard have been thoroughly studied.
Keywords: proverbs; phraseological units; nominative units